APPLICATION OF ELEMENTS OF THE CONTROLLED FROM DISTANCE STUDY DURING ORGANIZATION OF EDUCATIONAL PROCESS AT HIGH SCHOOL - Заміховський, Леонід Михайлович; Ходак, Любомир Мирославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This work presents theory of creating distance electronic courses with elements of behavioural learning and problem-oriented approach by using electronic course for subject “Modern technologies of software development.”